Analisis Yuridis Penyitaan Pidana Terhadap Boedel Pailit dalam Perspektif Hukum Kepailitan - Naomi Ida Gracia Nainggolan; Rosalinda Elsina Latumahina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The criminal seizure of a debtor's assets that have been declared bankrupt and constitute the bankruptcy estate remains a controversial legal issue in Indonesian law enforcement. This issue arises from the overlap of authority between criminal law and bankruptcy law in determining the party authorized to control and administer the debtor's assets. On the one hand, Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations stipulates that, upon the declaration of bankruptcy, the authority to administer and manage the bankruptcy estate is transferred to the receiver (curator) under the supervision of the supervisory judge. On the other hand, the Indonesian Criminal Procedure Code authorizes investigators to seize property allegedly connected with a criminal offense. This study aims to analyze the legal regulation governing criminal seizure of the bankruptcy estate, examine the legal status of the bankruptcy estate in criminal seizure proceedings, and evaluate the legal protection afforded to creditors against such seizures. This research employs a normative legal research method using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed qualitatively through descriptive-analytical methods. The findings indicate that criminal seizure of assets included in the bankruptcy estate is legally permissible provided that it complies with criminal procedural law. However, its implementation must also uphold the bankruptcy law principles of paritas creditorum and pari passu pro rata parte to prevent arbitrary impairment of creditors' rights.